Influence of metal surface preparation on the flexural strength and impact damage behaviour of thermoplastic FRP reinforced metal laminate made by press forming. (15th September 2019) - Santhanakrishnan Balakrishnan, Venkateswaran; Obrosov, Aleksei; Kuke, Felix; Seidlitz, Holger; Weiß, Sabine
Abstract: In this paper the relationship between surface energy and flexural strength of metal laminate made by reinforcing glass fibre reinforced polymer on steel surfaces was investigated. Sand blasting was performed on 22MnB5 steel surface. This steel was stacked together with layers of unidirectional glass/polyamide-6 prepreg, followed by pressing in a hot press. Influenced parameters are pressure, temperature and time. 3D profilometer analysis was used to investigate the roughness profile on the surface of the steel generated by the sand blasting. The surface energy of the steel surface was calculated from a set of contact angles measured by three different liquids. To identify the optimal surface treatment, the variation of surface energy, flexural strength and roughness of the steel surface was determined as function of the surface treatment. Surface roughness (Ra of 1.08 μm), results indicate that increasing surface roughness leads to improvement in flexural modulus. The increase further leads to decrease in flexural modulus. In addition, the influence of surface energy and flexural strength on the impact damage behaviour was investigated too. The results showed that the sample with highest flexural modulus had the lowest impact-induced damage area.